Gender differences in trunk appearance perception and health-related quality of life (HRQoL) in the patients with moderate adolescent idiopathic scoliosis (AIS) undergoing orthotic treatment: An observational study - JoJo Yiying Zou; Tung LI; Man Sang Wong (PLoS ONE, 2025)
Background Orthotic treatment is commonly used as a non-surgical intervention for managing moderate adolescent idiopathic scoliosis (AIS). Although prior studies have evaluated various factors influencing health-related quality of life (HRQoL) in the patients with AIS, the association between trunk appearance perception and HRQoL, including potential gender differences, remains insufficiently defined. This study investigated gender differences in trunk appearance perception and its relationship with QoL among the patients with moderate AIS undergoing orthotic treatment. Methods Patients with moderate AIS undergoing orthotic treatment were included, and HRQoL evaluations were conducted before treatment, as well as one and seven months after the initiation of orthotic treatment. The evaluation tools included the Trunk Appearance Perception Scale (TAPS), Scoliosis Research Society-22r (SRS-22r), and Brace Questionnaire (BrQ). The study time points were selected to capture baseline conditions, initial adaptation, and longer-term treatment effects. Results A total of 34 females and 11 males participated in the study. No significant gender differences were observed in global HRQoL, with both groups consistently reporting low self-image and self-esteem. In females, increasing age was negatively correlated with TAPS scores, whereas in males, it showed a positive correlation. For females, higher compliance was associated with higher bodily pain scores on the BrQ (ρ = 0.417), indicating reduced pain levels. In contrast, among males, greater compliance was associated with poor trunk appearance perception after seven months (ρ = −0.619). While TAPS was unrelated to SRS-22r and BrQ in females, a more favorable trunk appearance in males was strongly related to better function and self-image scores on the SRS-22r after seven months (ρ = 0.614 and 0.703, respectively). Conclusion Trunk appearance perception and overall HRQoL were similar between females and males in this study. However, the score related to self-image was lower than other HRQoL domains.